The use of urinary fluoride excretion to facilitate monitoring fluoride intake: A systematic scoping review. - Oladipo S Idowu; Liane B Azevedo; Ruth A Valentine; Josie Swan; Priyanka V Vasantavada; Anne Maguire; Fatemeh V Zohoori (PLoS ONE)
Background As a recognised effective and economical agent for dental caries prevention, fluoride has been used in many different fluoridation schemes implemented across the world. Considering the narrow 'dose-gap' between the benefit of caries reduction and the risk of dental fluorosis, it is recommended that fluoride intake is monitored by measuring urinary fluoride excretion. The aim of this scoping review is to map the current literature/evidence on fluoride intake and excretion studies in relation to the study population, settings, type of study design, methodology, and analytical approach. Methods Embase/Ovid, MEDLINE/Ovid, CINAHL/EBSCO, Scopus/Elsevier were searched for relevant articles until April 2018. Studies were included if they reported intake and excretion of fluoride in healthy humans of all age groups. Findings were explored using a narrative synthesis to summarise studies characteristics and outcome measures. Results Removal of duplicates from the originally 2295 identified records yielded 1093 studies of which 206 articles were included. Only 21.6% of the studies were conducted in children (<8-year-olds). Most studies (38.8%) used drinking water concentration as a proxy for fluoride intake, whereas only 11.7% measured fluoride intake from all sources. Of the 72 studies that measured dietary fluoride intake, only 10 reported the validity of the employed dietary assessment method. Only 14 studies validated the urine sample collection methods. No information on the validity of the employed analytical method was reported by the majority (64.6%) of studies. Only a small proportion (8.7%) of the included studies investigated the association between fluoride intake and excretion. Conclusion The findings reveal much variability in terms of conducting the studies and reporting the findings, illustrating a high heterogeneity in data collection across settings and populations. Future studies should provide more detail on sampling technique, measurement protocols (including validation), and on clearly defining the relationship between intake and urinary excretion of fluoride.